Types of Phrases in the Song Lyrics “Selalu Ada di Nadimu” (OST Jumbo) by Bunga Citra Lestari - Mayasari, Ira (The Future of Education Journal, 2025)
The purpose of this study is to describe the types of phrases found in the lyrics of the song “Selalu Ada di Nadimu” (OST of the film Jumbo) by Bunga Citra Lestari. The method used in this research is a descriptive qualitative method, which aims to illustrate and formulate library data regarding the types of phrases in the song lyrics. This descriptive research employs content analysis techniques to identify the types of phrases in the lyrics based on documents or text. The results of the study show that 18 instances of attributive endocentric phrases and 5 instances of exocentric phrases were found. Coordinative and appositive types of endocentric phrases were not found in this study.